Review of the genus Singilis Rambur, 1837 of North Africa and Iberian Peninsula (Coleoptera: Carabidae: Lebiini) - Anichtchenko, Alexander (Zootaxa, 2017)
The paper deals with the taxonomy of bicolor-group of species of genus Singilis Rambur, 1837 known from North Africa and South Spain. The species S. soror Rambur, 1837 is treated as polytipic and one new combination and new synonymy are proposed: S. soror melillensis Escalera, 1914 comb. n., S. pardoi Mateu, 1954 syn. n. = Singilis soror riffensis Mateu, 1954 syn. n. = S. soror soror Rambur, 1837. A new subspecies from Algeria is described: S. soror oranensis ssp. n. A key to species and subspecies is provided and the taxonomic position of these taxa is discussed.